2016
DOI: 10.7150/ijbs.14996
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-Derived Proteases in the Microenvironment of Pancreatic Cancer -Active Players in Tumor Progression

Abstract: A hallmark of pancreatic ductal adenocarcinoma (PDAC) is the fibro-inflammatory microenvironment, consisting of activated pancreatic stellate cells, extracellular matrix proteins, and a variety of inflammatory cells, such as T cells, macrophages, or neutrophils. Tumor-infiltrating immune cells, which are found in nearly all cancers, including PDAC, often fail to eliminate the tumor, but conversely can promote its progression by altering the tumor microenvironment. Pancreatic cancer cells are able to attract po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 135 publications
(157 reference statements)
1
72
0
1
Order By: Relevance
“…This is in agreement with previous reports showing that in the pancreas of mice fed a high-fat diet, fibrosis is also accompanied by inflammation in early-stage neoplastic lesions (43, 44); and with our previous observation that metformin reduces IL-1β and desmoplasia in tumors implanted in obese mice (50). It was shown before that neutrophil infiltrates can be observed in the vicinity of tumor cells and in the desmoplastic tumor stroma, which correlates with undifferentiated tumor growth and poor prognosis (51). We found that TAN specific depletion reduces PSC activation and the number of αSMA-positive cells associated with collagen I.…”
Section: Discussionmentioning
confidence: 98%
“…This is in agreement with previous reports showing that in the pancreas of mice fed a high-fat diet, fibrosis is also accompanied by inflammation in early-stage neoplastic lesions (43, 44); and with our previous observation that metformin reduces IL-1β and desmoplasia in tumors implanted in obese mice (50). It was shown before that neutrophil infiltrates can be observed in the vicinity of tumor cells and in the desmoplastic tumor stroma, which correlates with undifferentiated tumor growth and poor prognosis (51). We found that TAN specific depletion reduces PSC activation and the number of αSMA-positive cells associated with collagen I.…”
Section: Discussionmentioning
confidence: 98%
“…Elevated expression of MMP-9 is associated with cancerous and inflammatory microenvironments, including PDAC [26]. We aimed to use the presence of active MMP-9 in the tumor microenvironment to potentiate targeted delivery and infiltration of NPs into the tumor tissue of pancreatic cancer patients.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the concept of a predominantly pro-tumoral role of neutrophils and their derived products in tumor biology may be drawn from a small slice of the total physiologic functions of neutrophils, leaving other equally important aspects to be overlooked. For example, the pro-tumoral functions of neutrophil-derived proteases, including neutrophil elastase, have been attributed to their ability to degrade cytokines, chemokines, and their receptors, remodel the extracellular matrix, increase angiogenesis, and promote metastasis [3032]. A study by Houghton and colleagues showed neutrophil elastase uptake by lung adenocarcinoma cells, where it localized to endosomes and induced tumor cell proliferation by cleaving insulin receptor substrate-1, inducing hyperactivity of the phosphatidylinositol-3-kinase (PI3K) pathway and uncontrolled proliferation [33].…”
Section: Complexities In Understanding the Granulocytes In Human Cancmentioning
confidence: 99%